Analisis SWOT rencana strategis Baitul Maal wat Tamwil dalam mengembangkan ekonomi Islam - Sarif, Reza; Kusuma, Muhammad Alfarizi; Mubarak, Israul (Maliki Interdisciplinary Journal, 2024)
Baitul Maal wat Tamwil (BMT) is a financial institution that operates based on Sharia principles to provide financial services to the community. The research aims to compare the strategic plans implemented by Baitul Mal wat Tamwil (BMT) through SWOT analysis. The research results show that these three institutions have a strong commitment to expanding members’ business markets and a good understanding of sharia banking operations. However, they need to improve the quality of human resources and overcome business competition. Opportunities include member business market growth and increased member welfare, while threats include competition from other financial institutions, regulatory changes, economic risks, competition between Sharia cooperatives, and the impact of rapid information technology.